2018
DOI: 10.1002/anie.201802891
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Asymmetric Dearomatization by Visible‐Light‐Activated [2+2] Photocycloaddition

Abstract: A novel method for the catalytic asymmetric dearomatization by visible-light-activated [2+2] photocycloaddition with benzofurans and one example of a benzothiophene is reported, thereby providing chiral tricyclic structures with up to four stereocenters including quaternary stereocenters. The benzofurans and the benzothiophene are functionalized at the 2-position with a chelating N-acylpyrazole moiety which permits the coordination of a visible-light-activatable chiral-at-rhodium Lewis acid catalyst. Computati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
78
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 169 publications
(86 citation statements)
references
References 59 publications
1
78
0
1
Order By: Relevance
“…Based on the aforementioned efforts along with previousr eports, [4][5][6]26] ap ossible mechanism can be proposed to elucidate the reactionp rocess and chiral induction. As shown in Scheme3b, the substrate 1a coordinates to the chiral terbium-N,N'-dioxide complex to form the new photoactive chiral complex I.T his complex is readily excited by visible light to reach its lowest singlet state (S 1 ,i ntermediate II).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on the aforementioned efforts along with previousr eports, [4][5][6]26] ap ossible mechanism can be proposed to elucidate the reactionp rocess and chiral induction. As shown in Scheme3b, the substrate 1a coordinates to the chiral terbium-N,N'-dioxide complex to form the new photoactive chiral complex I.T his complex is readily excited by visible light to reach its lowest singlet state (S 1 ,i ntermediate II).…”
Section: Resultsmentioning
confidence: 99%
“…[2] To date, several successful strategies for asymmetric catalytic [2+ +2] photocycloadditions have been developed separately by the groups of Bach, [3a,b,d, 4] Yoon, [5] and Meggers. [6] Bach and co-workersf irst addressed this reactiont hrough the use of either chiral hydrogen-bondingo rganic sensitizers [3] or chiral Lewis acids [4] as catalysts. The key point of chiral Lewis acid catalysis is the bathochromic shift of the UV absorption of the catalyst-activated substrate, which enables unselective backgroundr eactions to be suppressed throughc areful irradiation with al ight source of appropriate wavelength.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…by molecular oxygen regenerates the ground state photocatalyst and produces the superoxide anion. Nucleophilic capture of A by N ‐hydroxycarbamate 2 a delivered the oxygen and alkene‐stabilized radical B , which undergoes single‐electron oxidation by superoxide anion and subsequent deprotonation to give the dearomatized product 3 a .…”
Section: Methodsmentioning
confidence: 99%
“…Very recently, Meggers group [13] demonstrated that visiblelight activated [2 + 2] photocycloadditions can be applied to catalytic asymmetric dearomatization reactions of benzofurans with styrenes (Scheme 2). This novel method provides very high enantioselectivity (98%À99% ee) and forms the tricyclic structures of N-acylpyrazole moieties with up to four stereocenters including a quaternary one.…”
mentioning
confidence: 99%